Uganda Nutrition Action Plan III for 2021-2026 includes strategies to increase adoption of biofortified crops - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The Plan provides the framework for addressing nutrition issues in Uganda sequentially to develop strong and quality human capital that will propel socioeconomic transformation.